2011
DOI: 10.1007/s00418-011-0778-2
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of small bowel resection: a unique histological study in a piglet model of short bowel syndrome

Abstract: If we are to develop successful interventions to improve clinical outcomes for short bowel syndrome patients we require (1) knowledge of changes within the epithelial population following small bowel resection (SBR) and (2) an idea of when these changes occur to inform on the timing of potential interventions aimed at enhancing the adaptive response. The aim of this study was to produce a temporal map of epithelial changes within the crypt and villus at early and late adaptation phases. Four-week-old piglets u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…There was no difference in goblet cells per hemivillus between sham and SBS groups. Previous studies have reported significant increase in goblet cell density in mouse and pig SBS models (17,33), but increases in goblet cells are also noted in response to ATOH1 and SPDEF (12,21).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There was no difference in goblet cells per hemivillus between sham and SBS groups. Previous studies have reported significant increase in goblet cell density in mouse and pig SBS models (17,33), but increases in goblet cells are also noted in response to ATOH1 and SPDEF (12,21).…”
Section: Discussionmentioning
confidence: 89%
“…The majority of investigations involve 50% or greater small bowel resection (SBR) in mouse, rat, and pig models. Piglet models benefit from the larger size of the animals, which allows a technically easier bowel resection and anastomosis, and authors also cite more anatomical, physiological, and biochemical similarities to newborn human infants than rodent models (33). However, housing, procurement, and surgical supplies are more expensive, typically thousands of dollars per piglet.…”
Section: Discussionmentioning
confidence: 99%
“…Piglets were fed a polymeric infant formula diet (Karicare De-Lact, Nutricia) supplemented to meet the daily requirements for piglets as described previously. 11,37,38 The diets were isocaloric and isonitrogenous among the groups and were administered on a per kilogram basis. Water was given twice daily.…”
Section: Methodsmentioning
confidence: 99%
“…Colonic tissue was collected 3 cm and 10 cm distal to the cecum in the two-week and six-week groups, respectively, at locations optimised for age, as based on a previous study. 37 A 3 cm section from each site was divided in half longitudinally and fixed in 10% neutral buffered formalin (Australian Biostain Pty. Ltd.) or snap frozen in liquid nitrogen.…”
mentioning
confidence: 99%
“…In the last decade, modern therapeutic options such as tissue engineering [9] have been among the topics of interest. Due to the anatomical and physiological similarities to humans, porcine models are useful for optimizing different therapeutic approaches [10,11,12,13,14]. There are various and sometimes not exact definitions of SBS in the literature.…”
Section: Introductionmentioning
confidence: 99%